Nanoparticulate Mucoadhesive System: Innovative Approach in Drug Delivery - Vikas S. Bhosale; Dr. Vishweshwar Dharashive; Londhe, Gajanan D; Kishor A. Sagale; Amruta S. Natkar; Amruta V. Magar; Kartale, Gangaram H. (Asian Journal of Pharmaceutical Research and Development, 2025)
Hepatic first pass metabolism and enzymatic degradation of the numbers of drugs leads to low systemic bioavailability in systemic circulation. To avoid this issue in drug delivery systems various modified drug delivery devices has been developed by pharmaceutical research scientists. But in last decade much more attentiveness has been focused towards the formulation and development of modified drug delivery systems by oral route because oral route is main and mostly preferred route of drug administration to the patients, So Nanoparticulate mucoadhesive system is one of the most innovative and novel approach in drug delivery. This Nanoparticulate mucoadhesive system avoids the hepatic first pass metabolism and enzymatic degradation of the drugs which may leads to enhanced systemic bioavailability. Conventional buccal drug delivery devices having lots of demerits to overcome this buccal film are formulated by using different excipients. Solvent casting, solid dispersion, semisolid casting, melt extrusion and rolling methods are used for the formulation and development of this mucoadhesive drug delivery system. This review provides an updated and up to date information with respect to the mechanism of mucoadhesion, selection of excipients, methods of preparation, evaluation parameters and unique applications of buccal film as a drug delivery device in treatment of various life threating diseases. At the last this review concludes the current issues, possible future investigation and scope in the field of pharmaceuticals.